2001
DOI: 10.1021/la001028r
|View full text |Cite
|
Sign up to set email alerts
|

Water Vapor Adsorption on the Sol−Gel Composites Prepared Using Ethyl Silicate 40 as a Silica Precursor

Abstract: Effective mesoporous composite adsorbents of water vapor can be prepared using a novel “one-pot”, sol−gel procedure with ethyl silicate 40 as a silica precursor. The multilayer mechanism of water adsorption appears to be responsible for high adsorption of water on the prepared samples. In the case of the lithium bromide doped samples this adsorption takes the form of a volume filling. The Dubinin−Astakhov equation very well portrays adsorption of water by the synthesized composites in relative pressures <0.3. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…In this case an X-ray amorphous phase of the confined salt was formed even in large pores (10 d av 50 nm) [11]. During water sorption, the composition of the hydrated X-ray amorphous salt is changing monotonically, and no stable crystalline hydrates are observed [10,11]. The possible reason for the formation of the X-ray amorphous phase is likely to be the strong interaction between salt and silica during sol and gel formation or impregnation of the matrix.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…In this case an X-ray amorphous phase of the confined salt was formed even in large pores (10 d av 50 nm) [11]. During water sorption, the composition of the hydrated X-ray amorphous salt is changing monotonically, and no stable crystalline hydrates are observed [10,11]. The possible reason for the formation of the X-ray amorphous phase is likely to be the strong interaction between salt and silica during sol and gel formation or impregnation of the matrix.…”
Section: Introductionmentioning
confidence: 92%
“…The sol-gel process [7][8][9][10][11] and impregnation procedure [12][13][14][15] are widely used to synthesize nanocomposites based * Corresponding author. Fax: +7 3833 309 573.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, Alié et al , observed that strong gel structures can readily be prepared by incorporating an additive, for example, 3-(2-aminoethylamino)propyltrimethoxysilane, during the synthesis of the gel to induce the nucleation mechanism related to the difference in reactivity between the additive and main silica precursors, tetramethyl orthosilicate (TMOS) or tetraethyl orthosilicate (TEOS). Also, more recently, we have observed that pores (and pore volumes) in hybrid xerogels and aerogels synthesized using ethyl silicate 40 (ES) were notably larger than those in the corresponding materials synthesized using TEOS alone. The ES is a common commercial form of ethoxypolysiloxane . As it is environmentally benign and available at prices competitive to those of most common silica precursors (i.e., TEOS and TMOS), it seems rational to carry out more systematic studies of the potentials of the application of ES and prepolymerized silica precursors, in general, in the synthesis of low-density silica xerogels.…”
Section: Introductionmentioning
confidence: 99%